Wie teuer ist eine mangelhafte Schleppermotorauslastung? - Schäfer, Winfried (de, 1980)
The optimal combination of tractor and implements is not easy. On one hand, the type and state of soil plays an important role in the transmission of the drawbar pull; on the other hand, there are rather inaccurate data on the power requirements of the implements. On the farm it is often necessary to use the available tractors and implements, which do not necessarily fit together. Using a soil-tilling example, the economic appraisal of inadequately used tractor power is presented in this paper.
What is the Price for Taking Poor Advantage of the Tractor Engine Capacity?
Keywords: Ra; käyttöaste; moottorit; traktorit; kustannukset; tractor utilization; engin power; cost